Controllable synthesis of flower-like MoSe2 3D microspheres for highly efficient visible-light photocatalytic degradation of nitro-aromatic explosives. Issue 24 (4th June 2018) - Huang, Jingwen; Jin, Bo; Liu, Huiqiang; Li, Xiaojuan; Zhang, Qingchun; Chu, Shijin; Peng, Rufang; Chu, Sheng
Abstract : The nitro-aromatic explosives of NB, PNP and 2, 4-DNP (40 mg L −1 ) could be completely degraded by MoSe2 3D microspheres for 3.5 h, 1.5 h and 2.5 h, under visible light irradiation. Abstract : Nitro-aromatic explosives existing on the surface of the Earth are difficult to degrade, and they greatly harm the ecological environment and human security. Herein, we successfully conducted the large-scale synthesis of novel flower-like MoSe2 3D microspheres and nanospheres by a simple hydrothermal method. The two types of MoSe2 3D spheres had a high crystal quality with abundant nanosheets, and their diameters were approximately 1.5 μm and 300–400 nm, respectively. The Brunauer–Emmett–Teller (BET) and UV-vis diffuse reflectance spectra (UV-vis DRS) analyses revealed that the specific surface area and the band gap of MoSe2 microspheres and nanospheres were 33.3 m 2 g −1 and 1.68 eV and those of the nanostructures were 13.6 m 2 g −1 and 1.52 eV, respectively. Moreover, two different morphologies of MoSe2 were used for the degradation of nitrobenzene (NB), p -nitrophenol (PNP) and 2, 4-dinitrophenol (2, 4-DNP) through a photocatalytic process. The results demonstrated that the three nitro-aromatic explosive solutions NB, PNP and 2, 4-DNP (40 mg L −1 ) could be completely degraded by MoSe2 3D microspheres under visible-light irradiation in 3.5 h, 1.5 h and 2.5 h, and the degradation time for MoSe2 nanospheres was 4.5 h, 2.5 h and 4 h, respectively. The mechanism of the photocatalytic reaction was also investigated in detail, and the photocatalytic degradation process was found to follow the pseudo-first-order kinetics. Our study demonstrated the potential application of MoSe2 microspheres as a photocatalyst for the degradation of nitro-aromatic explosives and other organic contaminants.